Efecto de la temperatura sobre el crecimiento de semillas de cacao - Boroughs, H.; Hunter, J.R.; Labarca, César; Dongo D., Segundo; Osores D., Arturo; Diez Altares, Carmen; Alvim, Paulo de T.; Moh, C.C.; Bazan de Segura, Consuelo; Corrales Macedo, Alejandro; Figarella, Jacinto (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
A study of the response of seeds of a single clone of cacao to temperature, in a water batch, showed that cacao seeds are very sensitive to cold. As little as four minutes at 2 grade centigrade decreased the viability to 6 percent. Sixteen minutes at 8 grade centigrade also reduced the viability to 6 percent. At the higher temperatures, it was found that 16 minutes at 52 grade centigrade was completely lethal.